What love has to do with it? - Edna Manley College of the Visual and the Performing Arts.; School of Arts Management & Humanities
This programme was done for the 6th Gender and Development Lecture entitled "What Love Has To Do With It?" The lecture was held on Thursday, March 5, 2015, at the Vera Moody Concert Hall.
Keywords: Programme. -- Jamaica